Facile synthesis of three-dimensional (3D) interconnecting polypyrrole (PPy) nanowires/nanofibrous textile composite electrode for high performance supercapacitors. (October 2017) - Liu, Qiongzhen; Wang, Bo; Chen, Jiahui; Li, Fei; Liu, Ke; Wang, Yuedan; Li, Mufang; Lu, Zhentan; Wang, Wenwen; Wang, Dong
Abstract: In present work, polypyrrole (PPy) has been in-situ polymerized on a poly(vinyl alcohol- co -ethylene) (PVA- co -PE) nanofirous textile to form a 3D interconnecting PPy nanowires/nanofibrous textile composite electrode (designated as NW-PPy/NFs/PET). It demonstrates that the introduction of anthraquinone-2-sulfonic acid sodium (AQS) can tune the morphology of PPy from nanospheres to nanowires. The resulting PPy@PVA- co -PE conformal nanofibers act as bridges among intertwined PPy@PET fibers and PPy nanowires, leading to continuous pathways for ion/electron transfer and larger surface area for faradic reaction. Benefiting from this unique structure, the two-electrode supercapacitor using NaCl solution as electrolyte delivers a high power density of 800 W kg −1 at an energy density of 20 W h kg −1 per mass of active materials. Furthermore, the symmetric all-solid-state NW-PPy/NFs/PET supercapacitor demonstrates high flexibility and cycle stability. Therefore, this work may open a new way to develop light weight and cost-effective electrodes for flexible energy storage devices.